Energy, exergy, economic and environmental analysis of a novel direct-expansion solar-assisted flash tank vapor injection heat pump for water heater. (15th February 2022) - Chen, Jiaheng; Zhang, Zhenya; Zhang, Guojie; Wang, Dingbiao
Highlights: A direct-expansion solar-assisted flash tank vapor injection heat pump is presented. 4E analysis on the presented system is conducted by simulation method. The presented system can improve heating performance by utilizing solar energy. The exergy performance of the presented system and all the components are analyzed. Abstract: Energy, exergy, economic and environmental analysis of a novel direct-expansion solar-assisted flash tank vapor injection heat pump for water heater is conducted by simulation method. Two working modes are designed for the presented system. The solar-assisted mode is recommended for most solar radiation conditions, and the air-source mode maintains more superior performance under extremely low or no solar radiation situations. By utilizing solar energy, the system heating efficiency and capacity can be respectively improved by up to 29.6% and 25.9% under the considered condition. The performance analysis shows that the presented system can respectively enhance the average heating capacity and efficiency by 11.7% and 10.6% in a typical winter day of Lanzhou City, compared with the conventional flash tank vapor injection heat pump system. The exergy analysis expresses that the heat exergy output increases with the solar radiation intensity, while the system exergy efficiency presents an opposite variation trend because of the greater increment of the exergy destruction in the solar collector. The economic analysis indicates that the presented system achieves a payback period of 8 years under the given assumptions. Benefiting from the electricity consumption reduction, the presented system can remarkably reduce the carbon dioxide and air pollution emissions.